ANALISIS INDEKS BAHAYA GEMPA BUMI BERDASARKAN PGA PERMUKAAN DI KECAMATAN SANDEN KABUPATEN BANTUL D.I. YOGYAKARTA - Umar, Umar; Niyartama, Thaqibul Fikri; Wibowo, Nugroho Budi (Prodi Fisika Fakultas Sains dan Teknologi UIN Sunan Kalijaga Yogyakarta, 2021)
This research is motivated by the earthquake phenomena that have occurred in the Yogyakarta area due to the 2006 earthquake. This study aims to determine the earthquake hazard index based on the method developed by BNPB and JICA by making earthquake hazard distribution maps correlated with settlement maps. This research was conducted in Sanden District in the south of Bantul Regency. The BNPB and JICA methods utilize four main parameters, namely shear wave velocity at a depth of 30 meters (Vs30), Ground Amplification Factor (GAF), accelerated ground rock vibration (PGASB) and acceleration of surface ground vibration (PGA). Vs30 is obtained from the inversion method using microtremor measurement data, the Vs30 value is converted into a GAF value using the formula Midorikawa et al (1994), for PGASB it is obtained from the PUSKIM website, based on the earthquake hazard index mapping guide the Vs30 and PGASB values obtained if multiplied then will get the surface PGA value then the surface PGA value is reclassified by the type of class based on the BNPB and JICA methods. The results showed that the value of Vs30 ranged from 154.66 m / s to 260.80 m / s, GAF values ranged from 1.64 g to 2.09 g, PGASB values ranged from 0.52 g to 0.67 g, and PGA values surface ranges from 0.87 to 1.32 g. The earthquake hazard index covers the entire Sanden District with an index value of 1 and the highest distribution of settlements prone to earthquake hazards is in the entire study area.Keywords: Microtremor, Vs30, GAF, surface ground vibration acceleration (PGA), PGASB, earthquake.